Epidemiological and molecular description of nosocomial outbreak of COVID-19 Alpha (B.1.1.7) variant in Saudi Arabia. Issue 11 (November 2022) - Alsaedi, Asim; Alharbi, Maher; Ossenkopp, John; Farahat, Fayssal; Taguas, Roxanne; Algarni, Mousa; Alghamdi, Ahmad; Okdah, Liliane; Alhayli, Sadeem; Alswaji, Abdulrahman; Doumith, Michel; Al-Saed, Aiman; et al.
Abstract: Background: Nosocomial outbreaks frequently occurred during the Coronavirus disease 2019 (COVID-19) pandemic; however, sharing experiences on outbreak containment is vital to reduce the related burden in different locations. Objectives: This article aims at sharing a practical experience on COVID-19 outbreak containment, including contact tracing, screening of target population, testing including molecular analysis, and preventive modalities. It also provides an epidemiological and molecular analysis of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‑CoV‑2) infection outbreak in a tertiary care hospital in Saudi Arabia. Methods: The outbreak occurred in a non-COVID medical ward at a tertiary care hospital in Jeddah, Saudi Arabia, from 22nd March and 15th April 2021. The multidisciplinary outbreak response team performed clinical and epidemiological investigations. Whole-Genome Sequencing (WGS) was implemented on selected isolates for further molecular characterization. Results: A total of eight nurses (20 % of the assigned ward nurses) and six patients (16.2 % of the ward admitted patients at the time of the outbreak) tested positive for the SARS-CoV-2 virus based on PCR testing. The outbreak investigation identified strong evidence of an epidemiologic link between the affected cases. WGS revealed a set of spike mutations and deletions specific to the Alpha variant (B.1.1.7 lineage). All the nurses had mild symptoms, and the fatality among the patients was 50 % (three out of the six patients). Conclusions: The current nosocomial COVID-19 outbreak, caused by the Alpha variant, revealed multiple breaches in the adherence to the hospital infection control recommended measures. Containment strategies were successful in controlling the outbreak and limiting infection spread. Molecular analysis and genome sequencing are essential tools besides epidemiological investigation to inform appropriate actions, especially with emerging pathogens.